Optimization of Traffic Dikmas by the Kamsel Unit in Reducing Traffic Accidents in the Madiun Police Jurisdiction Area - Simatupang, David Sangap Hasiholan (Indonesian Journal of Police Studies, 2024)
The number of motorized vehicles in Indonesia has reached 148 million units, so this influences traffic accidents. One of the cities that has been influenced is the city of Madiun. In 2022, Madiun City will experience an increase in the number of traffic accidents of up to 40.98%. This research aims to determine the performance of the Madiun Police traffic security unit in implementing community service activities as well as to reduce the number of accidents at the Madiun Police. This research uses the concept of optimization, the concept of social education, and the concept of preventing traffic accidents. Meanwhile, the theories used are management theory and communication theory. The approach in this research is a qualitative approach with a descriptive-analytical research type. The informants in this research were the Head of the Madiun Police, the Head of the Traffic Unit for the Madiun Police, the Head of the Bin Ops for the Traffic Unit for the Madiun Police, Head of the Traffic Accidents Unit for the Madiun Police, and Head of the Traffic Unit for the Madiun Police Traffic Unit. Data collection techniques in this research are interviews, observation, and document study. The data analysis techniques used are data collection, data reduction, and data presentation. In this writing, the author concludes that the optimization in literacy education activities conducted by the community development and social order coordination unit (kamsel) within the jurisdiction of the Madiun Police Resort has not been achieved, both in terms of management elements, the application of basic management functions, and its communication.